Pengaruh Harga Minyak Dunia, Harga Emas Dunia Dan Inflasi Terhadap Indeks Harga Saham Gabungan (IHSG) Di Bursa Efek Indonesia (BEI) Periode 2018-2020 - Edwin Dilla Septiana; Budi Wahono; Arini Fitri Mustapita (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to examine the effect of world oil prices, world gold prices and inflation on the composite stock price index on the Indonesian stock exchange. The population used in this study are companies listed on the IDX (Indonesian Stock Exchange) from the period 2018-2020. The sample selection in this study used purposive sampling technique. The number of samples used is 36 data. The sampling criteria are based on data entered on the Indonesia Stock Exchange from the period 2018-2020. The results of this study indicate that (1) World Oil Prices, World Gold Prices and Inflation simultaneously have an effect on the Composite Stock Price Index variable for the 2018-2020 period. (2) The World Oil Price partially has a significant positive effect on the Composite Stock Price Index variable for the 2018-2020 period. (3) The Gold Price partially has a negative and insignificant effect on the Composite Stock Price Index variable for the 2018-2020 period. (4) Inflation partially has a positive and insignificant effect on the Composite Stock Price Index variable for the 2018-2020 period. Keywords : World Oil Price, World Gold Price, Inflation, Composite Stock Price Index